The Influence of Tax Planning, Leverage, Profitability, and Firm Size on Firm Value (Empirical Study of Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange in the 2019-2021 Period) - Sherly Santoso; Devica Pratiwi (DINASTI RESEARCH, 2023)
The company's goal is to get profits for the survival of the company and maximize firm value. In addition, the company's goal is to increase firm value and optimize wealth for shareholders. If the firm value is high, it can increase the wealth of shareholders. Even the food and beverage industry is defined as a leading manufacturing sector that contributes greatly to the national economy. The purpose of conducting this research is to determine the positive influence of tax planning, leverage, profitability, and firm size on firm value, listed food and beverage sub-sector manufacturing companies that have been listed on the IDX and the number of companies seen from SahamU. The approach used in the following research is the quantitative method and the samples selected using the purposive sampling method. The results of the study show that the third hypothesis (H3) which is accepted, namely profitability, has a positive effect on firm value. While the first hypothesis (H1), second (H2) and fourth (H4) are rejected, because partially tax planning, leverage, and firm size have no effect on firm value.